Chemical characterization and antioxidant potential of ecuadorian propolis. (November 2022) - Cuesta-Rubio, Osmany; Hernández, Ingrid Márquez; Fernández, Mercedes Campo; Rodríguez-Delgado, Irán; De Oca Porto, Rodny Montes; Piccinelli, Anna Lisa; Celano, Rita; Rastrelli, Luca
Abstract: The chemical composition and the antioxidant potential of Ecuadorian propolis samples (n = 19) collected in different provinces were investigated. HPLC-DAD-ESI/MS n and GC-EI-MS analysis of the methanol extracts enabled us to define six types of Ecuadorian propolis based on their secondary metabolite composition. 68 compounds were identified, 59 of which are reported for the first time in Ecuadorian propolis. The detected compounds include flavonoids, diterpenes, triterpenes, organic acid derivatives, alkylresorcinol derivatives and nemorosone. Plants belonging to genera Populus, Mangifera and Clusia seemed to be vegetable sources employed by bees to produce Ecuadorian propolis. Total phenolic content and antioxidant activity of propolis extracts were determined by the Folin-Ciocalteu assay and 2, 2-diphenyl-1-picrylhydrazyl and ferric reducing/antioxidant potential assays, respectively. As expected, the variable chemical composition affected the differences in terms of antioxidant potential. Graphical abstract: Image 1 Highlights: The chemical composition of Ecuadorian propolis samples (n = 19) were investigated. 68 compounds were identified by HPLC-DAD-ESI/MS n and GC-EI-MS analysis. 59 compounds were identified for first time in Ecuadorian propolis. Six types of Ecuadorian propolis were determined by chemical composition analysis. Positive significant correlations between antioxidant activity and TPC was observed.